O nowych miarach zaawansowania procesu starzenia się ludności - Abramowska-Kmon, Anita (Studia Demograficzne, 2011)
The main aim of the article was to review measures of the population ageing process. In the first part, traditional (conventional) measures of population ageing are presented (i.e. old-age rate, median age, ageing index, dependency ratios, potential support ratio, parent support ratio). These measures are based on chronological age and give a coherent picture of population ageing. However, they do not take into account changes in life expectancy. In other words, they are based on the assumption that a 65-year-old person in 2000 is considered to be just as old as a 65-year-old person in 1900. But the probability of surviving in these two years is different: the remaining life expectancy at age 65 was much higher in 2000 than in 1900. Therefore, the second part of the article presents the new (alternative) measures of population ageing, which are adjusted to life expectancy. In particular, it describes the following measures: proportion of the population in age groups that have a remaining life expectancy of 15 years or less (Prop. RLE15-), prospective median age, population average remaining years of life, and prospective old-age dependency ratio. In the last section, the results of a comparison between conventional and alternative measures are presented. The new measures indicate a slower pace of population ageing in the future than the traditional ones. Thus, the measures recommended for designing governmental programmes aimed at the elderly are the new measures, which take into account life expectancy.